(untitled) (Anclajes, 2025)
The novels Carcoma (2021), by Layla Martínez, and Temporada de huracanes (2017), by Fernanda Melchor share a series of features that arouse interest with a view to a comparative study. Among them, it focuses on the motif of the haunted house that, in both works, appears inhabited by the character of the witch. The two novels are interpretable from the framework of the Feminist Rereading of the Witch Hunt, since they propose updates of the witch and her characteristic attributes coded from feminist discourses. It studies how the locus of the haunted house dialogues with its representative tradition, while opening questions to rethink the home as a space of confinement for women.